Therapeutic Apheresis and Human Monoclonal Antibodies in Non-Immunologic Diseases.: TA, HMA in Non-Immunologic Diseases - Bambauer, Rolf; Schiel, Ralf; Salgado, Octavio S (British Journal of Healthcare and Medical Research, 2023)
Non-immunologic diseases such as nephrological, blood diseases, dyslipoproteinemia, cancer, infections, intoxications etc. have often a severe course or a bad prognosis. Since more than 45 years, therapeutic apheresis has led in combination with other therapies to a steady increase in survival rates. Therapeutic apheresis is indicated in the most of the non-immunologic diseases, and in all antibody-mediated diseases. Since the introduction of hollow fiber membranes, a complete separation of the corpuscular components, pathologic substances, antibodies, toxins etc. is reached. The mortality rate of severe non-immunologic diseases is reduced by therapeutic apheresis. Other new therapies are various human monoclonal antibodies alone or in combination with therapeutic apheresis. The pathological aspects, the first-line and second-lines therapies for non-immunologic such as nephrological, neurological, gastroenterological, hematological diseases, and others are shown. The guidelines of the Apheresis Applications Committee of the American Society for Apheresis are cited. Therapeutic apheresis and/or human monoclonal antibodies have shown to effectively cure severe diseases without immunologic origin.